FACTORS FOR THE DEVELOPMENT OF PERSONAL DETERMINANTS OF THE FORMATION OF MANAGERIAL COMPETENCIES AMONG YOUTH LEADERS - Inoyatova Saidakhon Rustam qizi (International Journal of Innovations in Engineering Research and Technology, 2023)
Leadership education is a crucial component of student development. There are many skills and competencies included in direction development. Student governance development (SLD), education provides students with opportunities to demonstrate and develop their leadership skills at a young age. There is currently an argument for combining student leadership development opportunities into the formal education model. To explore the changing landscape of supervision education, a literature review has been undertaken in order to provide working definitions, the importance and history of student direction development (SLD), providing governance education programs and how educators might engage in leadership education.